2022
DOI: 10.3390/ani12151926
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Bio-Economic Model to Demonstrate the Importance of Health Traits in Herd Management of Lithuanian Dairy Breeds

Abstract: Assessing the economic importance of traits is crucial for delivering appropriate breeding goals in dairy cattle breeding. The aim of the present study was to calculate economic values (EV) and assign the importance of health traits for three dairy cattle breeds: Lithuanian Black-and-White open population (LBW), Lithuanian Red open population (LR) and Lithuanian Red old genotype (LROG). The EV estimation was carried out using a stochastic bio-economic model SimHerd, which allows the simulation of the expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Other authors have also highlighted additional significant differences of morphological traits between the breeds [34,35]. A previous study [36], in which the economic values (EVs) of functional traits for the three Lithuanian dairy cattle breeds were derived, indicated that the economic values of energy corrected milk (ECM) were 0.16 €/kg for Lithuanian Black-and-White open population (LBW) and Lithuanian Red open population (LR) and 0.21€/kg for Lithuanian Red old genotype (LROG). The higher EV for LROG was caused by a lower feed intake and a lower milk yield, compared with LR and LBW, as it was assumed that a larger proportion of concentrated feed was needed to ensure the increased milk yield [36].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other authors have also highlighted additional significant differences of morphological traits between the breeds [34,35]. A previous study [36], in which the economic values (EVs) of functional traits for the three Lithuanian dairy cattle breeds were derived, indicated that the economic values of energy corrected milk (ECM) were 0.16 €/kg for Lithuanian Black-and-White open population (LBW) and Lithuanian Red open population (LR) and 0.21€/kg for Lithuanian Red old genotype (LROG). The higher EV for LROG was caused by a lower feed intake and a lower milk yield, compared with LR and LBW, as it was assumed that a larger proportion of concentrated feed was needed to ensure the increased milk yield [36].…”
Section: Discussionmentioning
confidence: 84%
“…A previous study [36], in which the economic values (EVs) of functional traits for the three Lithuanian dairy cattle breeds were derived, indicated that the economic values of energy corrected milk (ECM) were 0.16 €/kg for Lithuanian Black-and-White open population (LBW) and Lithuanian Red open population (LR) and 0.21€/kg for Lithuanian Red old genotype (LROG). The higher EV for LROG was caused by a lower feed intake and a lower milk yield, compared with LR and LBW, as it was assumed that a larger proportion of concentrated feed was needed to ensure the increased milk yield [36]. In practice, environmental and economic factors, such as poor housing system, inadequate feeding, heat stress and low milk prices, play a key role in the survival of the herd and influence the length of the productive life of cows [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation and selection by selection indexes is an important tool in dairy cattle breeding, as it allows combine information on several traits into a single value, which is used to make selection decisions (Mancin et al, 2022;Marašinskienė et al, 2022). The ideal breeding goal for dairy cat-tle remains the main topic of researches, although consensus on this issue is problematic and is intensively discussed in the scientific literature (Miglior et al, 2017;Cole and VanRaden, 2017;Cole et al, 2021).…”
Section: Introductionmentioning
confidence: 99%